Twelve Years of Fogarty-Funded Bioethics Training in Latin America and the Caribbean: Achievements and Challenges. (April 2014) - Saenz, Carla; Heitman, Elizabeth; Luna, Florencia; Litewka, Sergio; Goodman, Kenneth W.; Macklin, Ruth
The landscape in research ethics has changed significantly in Latin America and the Caribbean over the past two decades. Research ethics has gone from being a largely foreign concept and unfamiliar practice to an integral and growing feature of regional health research systems. Four bioethics training programs have been funded by the Fogarty International Center (FIC) in this region in the past 12 years. Overall, they have contributed significantly to changing the face of research ethics through the creation of locally relevant training materials and courses (including distance learning), academic publications, workshops, and conferences in Spanish, and strengthening ethics review committees and national systems of governance. This paper outlines their achievements and challenges, and reflects on current regional needs and what the future may hold for research ethics and bioethics training in Latin America and the Caribbean.